FORMULATION AND EVALUATION OF FINASTERIDE SUSTAINED-RELEASE MATRIX TABLETS USING DIFFERENT RATE CONTROLLING POLYMERS - Chibueze, Igwe J.; IV, Emenike; R, Oduola A (Universal Journal of Pharmaceutical Research, 2016)
Objective: Finasteride is chemically considered a synthetic 4-azasteroid drug used in the treatment of anti-hyperplasia. In matrix system of sustained release drug is dispersed homogenously throughout a polymeric matrix. The aim of the present investigation was to develop oral controlled release matrix tablet formulations of Finasteride with different polymer ratios. Methods: The granules were evaluated for angle of repose, bulk density and Compressibility index before being punched as tablets. Total 5 varieties o of tablets were compressed using polymers (HPMC, EC, Eudragit RS100) in different ratio. The tablets were subjected to weight variation test, drug content, hardness, friability, and in vitro release studies. Different models for kinetic study were applied like zero order, first order, Higuchi, Hixson Crowell and Korsmeyer to study the release pattern and mechanism. Results: All the formulations showed uniform thickness. In a weight variation test, the pharmacopoeial limit for percentage deviation for the tablets of more than 250 mg is ±5%. The formulation MT5 showed a comparatively high hardness value of 4.8±0.22 kg/cm2. Matrix tablets of batch MT1 shows maximum release 86.42% in 10 hrs. Conclusion: Observations of all formulations for physical characterization had shown that, all of them comply with the specifications of official pharmacopoeias and/or standard references. Study concludes that Finasteride can be delivered effectively in the form of matrix tablets. Peer Review History: Article received on- 8 October 2016; Revised on- 11 November; Accepted on- 14 December; Available online 15 January 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Barkat Ali Khan , Kampala International University , Uganda, barki.gold@gmail.com Dr. Dalia Kamal Zaffar Ali , Modern University for technology and information, Egypt, dr.moda88@gmail.com